Habitat Preferences of the Common Nighthawk (Chordeiles Minor) in Cities and Villages in Southeastern Wisconsin - (:unkn) unknown (My University, 2014)
Limited survey data and numerous anecdotal accounts indicate that the Common Nighthawk (Chordeiles minor) is experiencing population declines in Wisconsin. However, the magnitude of the decline is unclear because current avian monitoring efforts are not conducted at dusk when Common Nighthawks are most active nor do they specifically target urban areas such as cities and villages where Common Nighthawks are known to nest on flat graveled rooftops. New urban, crepuscular monitoring methods are needed in order to gain a better understanding of current Common Nighthawk demographics in Wisconsin. The goal of this thesis was to conduct a baseline study using citizen science – based methodology to determine where Common Nighthawks persist in cities and villages in southeastern Wisconsin. The objectives of the study were to collect information on environmental factors, landscape features, and land cover types of potential importance to Common Nighthawks during the breeding season and then analyze the data collected to investigate correlations between each variable and Common Nighthawk occurrence at each survey point. The aim was to use the findings of the baseline study to inform current avian monitoring efforts such as the Wisconsin Nightjar Survey so that adjustments allowing for more effective monitoring of Common Nighthawks could be implemented in survey route placement and survey protocol. Between June 7th and July 18th 2013, volunteers conducted 1,412 surveys at 494 points in 82 cities and villages within the Southeast Glacial Plains and Southern Lake Michigan Coastal ecological landscapes of Wisconsin. Common Nighthawks were detected in 98 surveys at 68 points in 32 cities and villages. On three different evenings at each point, volunteers conducted 10 – minute point counts in which they counted Common Nighthawks and described their behavior. During surveys, volunteers recorded the temperature ( ° F), estimated the moon phase, rated the sky condition, wind speed, noise, light pollution, and insect activity, and counted the number of potential Common Nighthawk predators (e.g. crows, gulls, raptors, and cats), and the number of Chimney Swifts. Volunteers also counted sources of artificial ambient light (e.g. street lights and stadium lights) and flat rooftops surrounding (100 meter buffer) the survey point. The land cover surrounding each survey point (500 meter buffer) was analyzed from the National Land Cover Database (NLCD) 2011 using Geographic Information Systems (GIS). The number and total area of flat graveled rooftops surrounding each point (500 meter buffer) were estimated from aerial photos taken in 2011 using GIS. Results from statistical analysis of land cover classes suggests that in cities and villages, Common Nighthawks are more likely to be found in areas with higher percentages of impervious or built-up land cover. Agricultural land cover was the only land cover class that demonstrated a statistically significant negative correlation with Common Nighthawk presence. Strong, statistically significant positive correlations were found between Common Nighthawk presence and both the number of flat graveled rooftops and the total area of flat graveled rooftops. Mann Whitney U analysis of environmental variables recorded by volunteers suggests a statistically significant negative correlation between Common Nighthawk presence and percent moon illumination. A statistically significant positive correlation was also found between Chimney Swift (Chaetura pelagica), counts and Common Nighthawk presence. A statistically significant positive correlation was also found between Common Nighthawk presence and the two landscape features measured by volunteers (100 meter buffer) – the number of flat rooftops, and the number of sources of artificial ambient light.
Keywords: Chordeiles Minor; Citizen Science; Common Nighthawk; Nighthawk; Nightjar; Urban Bird Survey